The Influence of Computer Based Management Information Systems on The Performance of Youth and Sports Offices in North Sumatra Province - Sri Indah Sari; Toni Hidayat (International Journal of Economics (IJEC), 2022)
The purpose of this study was to determine the effect of a computer-based management information system on the performance of North Sumatran youth and sports officials. The population in this study were employees of the youth and sports department of North Sumatra. totaling 156 people. The sample in this study amounted to 60 people taken randomly using random sampling technique. This type of research is quantitative research. The data collection instrument used a questionnaire and direct observation of the field which was then analyzed using a simple linear regression analysis method Y = 5.335 + 0.959X, which means that a computer-based management information system has an effect on employee performance. Furthermore, the results of the t-test showed 9.360 > 1.67, so it can be concluded that the computer-based management information system variable has a significant effect on employee performance. R square shows the coefficient of determination is 0.602, meaning that computer-based management information systems affect employee performance by 60.2%, while the remaining 39.8 is influenced by other variables not examined in this study.